Involving Suppliers in Product Development - Elçi, Oğuz (My University, 1999)
Yardımcı Sanayinin Ürün Geliştirme Sürecine Dahil Edilmesi Günümüzde yeni endüstri ürünlerinin ve teknolojinin yaratılmasının genelde bir firmanın işi değil, bir çok firmanın biraraya gelerek oluşturduğu bir teknoloji ortaklığının işi olduğunu görürüz. Değişik alanlardaki uzmanlıkları ile birbirlerinin tamamlayıcısı olan bu firmalar yenilik sürecinde değişik roller üstlenirler. Japonya'da üreticinin, yardımcı sanayileri ile birlikte oluşturdukları kerietsu denilen ağ şebekelere rastlarız. Bu tip tasarım ortaklıklarında, ortaklar birbirlerinin eksikliklerini tamamlayarak pazarda yeni ürün yaratmayı amaçlarlar. Yardımcı sanayilerin ürün geliştirme çalışmalarında yer aldığı 3 model vardır. 1. Klasik yardımcı sanayi- ana sanayi ilişkisi Her bir yardımcı sanayi üretimini, ana sanayinin talimat ve resimlerine tamamen sadık kalarak yapar. Bu durumda yardımcı sanayi, ana sanayinin uzak bir iş istasyonu gibidir. 2. Sistem tamamen yardımcı sanayi tarafından tasarlanır. Bu modelde bitmiş ürün, ana sanayi için kara kutu'dur. Yarı optimal bir sistemin geliştirilme tehlikesi vardır. Problem çözme işlemlerinin bir firma içine entegre olması dolayısıyla zaman ve maliyet avantajı yoktur. 3. Ortak tasarım Bitmiş ürün fonksiyonları organize bir yapıya parçalanarak ürün geliştirme ortaklığının konfigürasyonu ana sanayi tarafından belirlenmiş olur. Yardımcı sanayilerle ortak tasarıma gidilebilmesi için aşağıda bahsedilen 3 şartın gerçekleşmesi gereklidir. 3.1. Temel Uyum Ortakların, ortaklığın oluşturulması için gerekli olan birbirini tamamlayan ve rekabet yaratan özelliklerinin olup olmadığı araştırılmalıdır. 3.2. Stratejik Uyum Ortakların tasarım projesi üzerine kısa ve orta vade hedef ve beklentileri birbirleri ile uyum içinde olmalıdır. 3.3. Kültürel Uyum Değişik firma kültürlerinin birbirlerine uyabilirliği araştırılmalıdır. Etkili ve Verimli Ürün Geliştirme 1. Emniyetle Pazara (Sakin Ürün Geliştirme) Yüksek teknoloji ürünlerinin pazarda başarılı bir şekilde yer bulması uzun ve zahmetli kalite güvenilirlik çalışmalarının, yüksek yatırımların, kaynak ve bilginin bir eseridir. Böyle bir sistem üzerinde zaman baskısının olmadığı sakin bir ürün geliştirme süreci ister. 2. Hızla Pazara Pazardaki hırslı çekişme firmaları, ürünlerini pazara daha kısa zamanda, daha fazla yenilikle sunmaya zorlamaktadır. Fakat bunu başarmak için yüksek ivmeli ürün geliştirme süreçlerine ihtiyaç vardır. Bir tasarım ortaklığının amacı 1. Zaman Kazanımı 2. Maliyet Kazanımı 3. Kalite Kazanımı Önemli Ürün Geliştirme Stratejileri 1. Kırma Pazarda zaten güçlü bir rakip vardır. Bu nedenle mevcutta açık kapasiteler üzerine konsantre olmak gereklidir. 2. Adım adım yenilik Ortaklık dikey doğrultuda yeni pazarlar açmak umuduyla yapılır. Yardımcı sanayilerle ortaklığa gidilerek müşteri faydası arttırılmaya çalışılır. 3. Çekirdek sıçrama Düşük fırsat maliyetleri, rakip firmaların potansiyel pazarı daha farkedemediklerini göstermektedir. Ham alanlarda ortaklık gerekli bilginin toplanmasını sağlar. Riskin paylaşılması burada her iki taraf içinde önemli bir motivasyondur. Ürün tasarımı ortaklıklarının avantajları Üretici için : 1. Arge kapasitesini arttırır 2. Pazara ürün sunma süresini azaltır 3. Ürün tasarımı maliyet ve riskini azaltır 4. Rekabet gücünü arttırır 5. Yardımcı sanayinin güçlü olduğu uluslararası pazarlara girmeyi kolaylaştırır 6. Ürün kalitesi artar Ürün tasarımı ortaklıklarının avantajları Yardımcı sanayi için : 1. Alıcı satıcı iletişim bariyerlerini kaldırarak satışları arttırır 2. Malzeme ve parça üretimi için olanaklar yaratır. 3. Uzun vadeli satışlar ölçek ekonomisi yardımı ile fiyatları düşürmeye ve böylece karlı kalmaya yardımcı olur. Ürün tasarımı ortaklıklarının dezavantajları Üretici için : 1. Teknolojinin tümüne erişimi engeller 2. Tek kaynak malzemenin sürekliliği için bir tehlikedir 3. Tek kaynak en ucuz kaynak demek değildir 4. Korunamayan bilgi teknolojileri çalınabilir 5. Uygulama, tartışma ve devreye almak için çok zaman harcanır 6. Yardımcı sanayiye bırakılan aktivitelerde teknik yeterlilik kaybı Ürün tasarımı ortaklıklarının dezavantajları Yardımcı sanayi için : 1. İlişkiler yeni ürünün başarısına bağlanır 2. Yardımcı sanayinin teknik yeterliliği değil, müşterinin pazarlama stratejisi ürünün başarısını belirler 3. Ortaklar birbirine çok bağlı olurlar 4. Ortaklığın bilinmesi, diğer müşterileri korkutabilir 5. Uygulama, tartışma ve devreye almak için çok zaman harcanır 6. Yardımcı sanayiye bırakılan aktivitelerde teknik yeterlilik kaybı Arçelik'te örnek bir çalışma Arçelik - AKO ortak çamaşır makinası kontrol sistemi tasarımı Y19/ 25 projesinde Arçelik çamaşır makinalarının program cihazlarını ve buna bağlı olarak kontrol sistemlerini AKO ile birlikte geliştirme kararı aldı. Arçelik'in hazır bir sistemi almamasındaki sebep, Arçelik'in vizyonunda görülebilir. Arçelik 2005 yılına kadar Avrupa'nın önde gelen 5 üreticisi arasında yerini almak istemektedir. Bu ağır yük pazarda en iyilerle rekabet etmeyi gerektirmektedir. AKO'nun motivasyonu AKO konusunda Avrupa'nın en iyi üreticilerinden biridir. Yeni tasarlamaya başlayacağı program cihazı için iyi bir referans olacak tanınır bir ortak aramaktadır. Arçelik'in motivasyonu Arçelik tasarımda yer alarak, en son teknolojiye sahip olmayı amaçlamaktadır. Arçelik neticede bu ortaklıktan aşağıda sıralanan faydaları sağlamıştır. Daha kısa ürün geliştirme zamanı En son teknolojiye sahip olma ve bunu geliştirebilme Daha az mühendislik zamanı ve düşük maliyetlerden kaynaklanan ucuz fiyat Ortak tasarımların patentle korunumu İlk adım olarak Arçelik, ortak tasarım metodolojisini aşağıda bahsedilen 7 ana başlıkla oluşturmak istemektedir. 1. Yardımcı sanayinin mühendislik, araştırma, deneyim ve ortak tasarım için kabiliyetlerinin değerlendirilmesi 2. Anlaşma 3. Tasarım soru formu ve tasarımın kısıtları 4. FMEA, QFD, Değer mühendisliği 5. Proje takvimi ve iş dağılımı 6. Onay 7. Ödüllendirme Involving Suppliers in Product Development Today, creating new industrial goods and technology are in most cases not the result of one single firm's efforts but tend to be the outcome of an interorganizational technology cooperation in developing industrial products among two or several companies or organizations that have different but complementary resources which play different roles in the innovation process. In Japan, there are networks which are formed between the manufacturer and its outside suppliers. In these product development cooperations complemantary competences of partners are used to create product differentiation in the market. Three models of suppliers' involvement in product development 1. Classical contractor - subcontractor relation Each supplier produces in accordance with the contractor's exact specifications, and thus serves essentially as an extended work bench. 2. System is developed completely by the supplier In this case, the contractor regards the work, carried out by the supplier as a black box. There is a danger that only a sub-optimal overall system will be developed. Time-and cost-savings due to integrated problem solving are not achieved. 3. Cooperative development Configuration of the development partnership is provided by the contractor breaking down the functions of the finished products in to an organized structure. 3.1. Fundamental fit It must first of all be assessed whether the complimentary competences which are necessary for partnership-based cooperation are available. 3.2. Strategic fit The medium to long term objectives of the potential partners with regard to the development project must be compatible. 3.3. Cultural fit It must be ensured that the different corporate cultures are suited to one another. In order to form a development partnership, the below mentioned partnership potentials must be met. 3.1. Fundamental fit It must be assessed whether the complimentary competences which are necessary for partnership based cooperation are available. 3.2. Strategic fit The medium- to long-term objectives of the potential partners with regard to the development project must be compatible. 3.3. Cultural fit It must be ensured that the different corporate cultures are suited to one another. Effective and efficient product development 1. Safe to market (calm PD) The successful placement of high-tech products in the market is dependant on a rigorous system of quality assurance which involves a high level of investment in terms of time, resources, costs and know-how. Such a system requires calm product development processes without any pressure of time (safe to market). 2. Fast to market The predatory competitive situation compels companies to launch their products on the market more quickly and with a higher level of innovation. But to achieve this, exceptionally high acceleration of product development times is necessary. Aim of a design cooperation 1. Time Benefits 2. Cost Benefits 3. Quality Benefits Important Development Strategies 1. Crash program A strong rival company is already present on the market. It is therefore necessary to concentrate on currently available capacities. 2. Step by step innovation Cooperation is to be carried out primarily in vertical direction, in order to open up new markets and to increase the benefit to the customer via cooperation with the buyers. 3. Quantum leap The low opportunity costs indicate that the rival companies have not yet discovered the potential market. Cooperation in core areas serves to develop the necessary know-how. The sharing of risks is also an important motive here, in view of the great uncertainty which prevails. Advantages of PD alliances For Manufacturer : 1. Augments R&D capability 2. Decreases time to market 3. Reduces new PD cost and risk 4. Increases competitive strength 5. Can facilitate entry to international markets where supplier is strong 6. Improved product quality Advantages of PD alliances For Supplier : 1. Makes sales easier by lowering seller-buyer communication barriers 2. Provides opportunities to build materials and parts 3. Long term sales allows more opportunity to reduce costs via economies of scale and experience curve effects and remain competitive Disadvantages of PD alliances For Manufacturer : 1. Limits access to all available technology 2. Single supplier is a potential risk to continuing supply 3. Single source may not be least cost alternative 4. Proprietary technology may have to be divulged that is not protectable 5. Time spent in negotiation, implementation, and integration 6. Potential loss of technical capability in activities allocated to supplier. Disadvantages of PD alliances For Supplier: 1. Relationship dependent upon success/ failure of new product 2. Customer marketing strategy, not supplier technical capability may be determinant in success/ failure 3. Supplier may become too dependent on one customer & vice-versa 4. Knowledge of collaboration may scare off other customers 5. Proprietary technology may be divulged that is not protectable 6. Time spent in negotiation, implementation and integration. A Sample Study in Arçelik Arçelik - AKO collaborative design for the control system of a washing machine In Y19/ Y25 project Arçelik prefered to develop a timer and the corresponding control system with AKO. The reason why we did not accept a ready solution lies in the vision of Arçelik. Arçelik wants to be in the first 5 appliance manufacturer of Europe by the year 2005. This hard job necessitates to compete in the market with the bests. AKO's motivation AKO was best in class supplier and seeking for a strong, well-known manufacturer for to be a reference for its new generation timer which will be first in industry with Arçelik. Arçelik's motivation By widely taking part in the control system design, Arçelik was aiming to have the latest technology in the market Arçelik benefited from the below mentioned assets at the end. Shorter development time Reaching to the latest available technology and advancing it Effective cost due to less engineering time and low development costs Common inventions will be protected by patents As the first step Arçelik thinks to form a methodology for co-design under the seven main topics. 1. Evaluation of the capability of the supplier in terms of engineering, research, experience for cooperative design 2. Contract 3. Questionnaire and the restrictions of design 4. FMEA, QFD, Value engineering 5. Project schedule and job allocation 6. Approval 7. Rewarding
Keywords: ÜRÜN YÖNETİMİ